Metionina e cistina para suínos dos 15 aos 30 kg - Muniz, Camila Francisca (2014)
Two experiments were carried out to evaluate levels of methionine and cystine on performance, depth of longissimus dorsi muscle, backfat thickness, biochemical parameters of blood, serum homocysteine and straightening of disulfide bonds in bristle of barrows and gilts in the initial phase. In each experiment, 70 barrows (Experiment I) and gilts (Experiment II) were used, with initial weight of 15.216 ± 0.540 kg and 15.193 ±0.580 kg, respectively, distributed in an experimental design of randomized blocks in a factorial scheme 2 x 3 + 1, with five replicates and two animals per experimental unit. Treatments were constituted by maintaining the ratio 1:1 among sulfur amino acids (DL-methionine and L-cysteine synthetic supplementation) or not (only DL-methionine supplementation), 3 levels of digestible met+cys (0.580, 0.640 and 0.700%) and a diet containing low level (0.520%) of digestible met+cys (basal diet). The basal diet (0.520% met+cys) was formulated to provide a 1:1 ratio of digestible methionine (0.26%) and digestible cystine (0.26%), being common to both treatments. In Experiment 1, the final weight answered (P=0.019) as a function of increasing dig met+cys levels when the relationship (50%) was not maintained between amino acids, which the highest value was obtained at the level of 0.663% dig met+cys. The maximum daily weight gain was obtained at the level of 0.661% dig met+cys (P=0.003) when the 1:1 ratio between the sulfur amino acids was not kept. Plasma glucose increased (P=0.006) as the levels of dig met+cys increased when the met:cys ratio was not kept in 50%. Total cholesterol decreased linearly (P=0.003) as the levels of dig met+cis increased in the diet, when the ratio was not kept between both, so that the lowest level of dig met+cys rated (0.52%) resulted in 64.00 mg/dL, and the highest level (0.70%) resulted in 50.30 mg/dL of plasma cholesterol. Homocysteine in the blood serum was not influenced (P>0.05) by treatments with either supplemental DL-methionine and L-cystine as only DL-methionine. In Experiment 2, the final weight presented linear increase (P = 0.017) for treatments which met:cys relationship was 1:1. However, for the treatments which relationships were not kept, the best final weight was obtained for the level of 0.589% dig met+cys. The depth of longissimus dorsi muscle presented increasing linear answer (P= 0.005) when levels of me+cys were evaluated which met:cys relationships were not constant. There was increasing linear effect (P=0.001) for plasma HDL as a function of dig met+cys levels in treatments which met:cys relationships was 1:1. We concluded that digestible methionine + cystine requirements for barrows from 15 to 30 kg is 7.88g/day, which corresponds to 0.661% in the diet, and for gilts, at the same phase, it is necessary an amount of 6.83 and 7.81g/day, respectively for better weight at the end of phase and depth of longissimus dorsi muscle, which corresponds to 0.589% and a minimum of 0.700%, respectively, without the need to keep the same ratio between sulfur amino acids for both sexes.